DFT based microkinetic modeling of confinement driven [4 + 2] Diels–Alder reactions between ethene and isoprene in H-ZSM5. Issue 24 (9th November 2022) - Rzepa, Christopher; Rangarajan, Srinivas
Abstract : Diels–Alder reactions between ethene and isoprene can be catalyzed on the Brønsted acid sites of H-ZSM5 primarily due to confinement. Abstract : We present a dispersion corrected periodic density functional theory investigation on the confinement driven catalysis of [4 + 2] Diels–Alder cycloaddition reactions between ethene and isoprene by H-ZSM5. A detailed reaction network, which included competitive chemisorption and oligomerization of the reactants, had been constructed; the reaction rates and product yields were inferred using microkinetic modeling. Our results show that the rates of Diels–Alder reactions were larger on the Brønsted acid sites of H-ZSM5 relative to their uncatalyzed reactions. This rate enhancement was driven by favorable dispersion interactions imparted by the framework on the transition states rather than their Brønsted–π interactions at the active site. A variance-based global sensitivity analysis showed that the formation of the C10 para -cycloadduct and its desorption were both kinetically controlling and mathematically correlated. Ultimately, this led to a negative apparent order with respect to isoprene for the C7 cycloadduct, and fractional orders for the remaining C10 cycloadducts.